High-elasticity composite polyester wadding and preparation method thereof
By adopting core-shell structure spray cotton adhesive adhesive and specific preparation steps, the problem of difficult control of the adhesive properties in the preparation of spray cotton is solved, and the preparation of high-elastic composite spray cotton is realized, which improves the quality and performance of the finished product.
Patent Information
- Application Number
- CN202411686152.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2025-02-25
AI Technical Summary
During the preparation of the glue spray cotton, the coagulation rate, crosslinking degree, contact angle and elasticity of the adhesive are difficult to control, resulting in unstable quality of the finished glue spray cotton.
Core-shell structure spray glue cotton adhesives are used to spray core and shell structures, including methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethylacrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, glycol butyl ether, ammonium water, NaHCO3, Na2CO3. Through specific preparation steps and spraying treatment, the uniformity and crosslinking of the adhesive are ensured.
It effectively improves the elasticity of the finished glue spray cotton, ensures that the coagulation rate, crosslinking degree, contact angle and elasticity of the adhesive are controlled, and improves the water absorption rate and overall performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of spray-bonded cotton, and in particular to a high-elasticity composite spray-bonded cotton and a preparation method thereof. Background Art
[0002] Spray-bonded cotton, also known as spray-bonded cotton, is a kind of non-woven fabric. The principle of the formation of the spray-bonded cotton structure is to spray the adhesive on both sides of the fluffy fiber layer. Due to the certain pressure during spraying and the suction force during the vacuum absorption of the lower part, the adhesive can also penetrate into the inside of the fiber layer. The fiber layer after spraying the adhesive is dried and cured, so that the intersection points between the fibers are bonded, and the fibers that are not bonded to each other still have a considerable degree of freedom. At the same time, in the three-dimensional network structure, there are still many gaps containing air. Therefore, the fiber layer has a porous and high-fluffy warm-keeping effect. Spray-bonded cotton, also known as spray-bonded cotton, is a kind of non-woven fabric, that is, the so-called space cotton or vacuum cotton. It is made of natural cotton fiber, artificial fiber or synthetic fiber through loosening, combing, spraying, baking and curing. Because of its fluffy, high compression resilience, resistance to dry and wet washing, and light weight and warmth retention, it has become an important material for processing and manufacturing cotton clothes and ski jackets, space suits and quilts, sleeping bags and other bedding and some industrial products in recent years.
[0003] When preparing spray-bonded cotton, the adhesive is more important, and the quality of the adhesive directly affects the overall quality of the spray-bonded cotton. However, when synthesizing the adhesive, its cohesion rate, cross-linking degree, contact angle and elasticity are all uncontrollable, which will affect the quality of the finished spray-bonded cotton. Summary of the invention
[0004] The main purpose of the present invention is to provide a high-elasticity composite spray-bonded cotton and a preparation method thereof, which can effectively solve the problems in the background technology.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A high-elastic composite spray-bonded cotton comprises a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, ethylene glycol butyl ether, ammonia water, NaHCO 3 、Na 2 CO 3The mixture comprises, by mass, 30-40 parts of methyl methacrylate, 20-30 parts of n-butyl acrylate, 2-5 parts of styrene, 2-5 parts of N-hydroxymethyl acrylamide, 3-8 parts of acrylic acid, 3-8 parts of disodium alkyl diphenyl ether disulfonate, 1-3 parts of nonylphenol polyoxyethylene ether, 1-3 parts of ammonium persulfate, 0.5-2 parts of ethylene glycol butyl ether, 5-10 parts of aqueous ammonia, 2-5 parts of NaHCO 3 , 0.2-3 parts of Na 2 CO 3 .
[0006] Preferably, the N-hydroxymethyl acrylamide is an industrial product, acrylic acid is analytically pure, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytically pure, ethylene glycol butyl ether is analytically pure, ammonia water is analytically pure, NaHCO3 is analytically pure, and Na2CO3 is analytically pure. The fineness of the fiber layer is 6.6-7.7 dtex, the length is 51-7 mm, the number of crimps is 0.5-0.6 per millimeter, and the hollowness is 5-10%.
[0007] Preferably, the mixture comprises, by mass, 30 parts of methyl methacrylate, 20 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 8 parts of acrylic acid, 8 parts of disodium alkyl diphenyl ether disulfonate, 3 parts of nonylphenol polyoxyethylene ether, 3 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 10 parts of aqueous ammonia, 5 parts of NaHCO 3 , 1 part of Na 2 CO 3 .
[0008] Preferably, the mixture comprises, by mass, 35 parts of methyl methacrylate, 25 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 5 parts of acrylic acid, 5 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 2 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 8 parts of aqueous ammonia, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 .
[0009] Preferably, the mixture comprises, by mass, 40 parts of methyl methacrylate, 30 parts of n-butyl acrylate, 2 parts of styrene, 2 parts of N-hydroxymethyl acrylamide, 3 parts of acrylic acid, 3 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 1 part of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 9 parts of aqueous ammonia, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 .
[0010] A method for preparing high-elastic composite spray-bonded cotton, comprising the following steps: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: Put a thermometer, condenser, stirring paddle and constant pressure dropping funnel into a four-necked flask, then place the four-necked flask in a constant temperature water bath, add emulsifiers such as disodium alkyl diphenyl ether disulfonate and Na 2 CO 3 , styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water, the speed is set to 400r·min -1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , add NaHCO evenly over 15 min. 3 , and keep warm for 20 minutes to complete the seed emulsion, the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer are evenly added to the seed emulsion within 2 hours, and kept warm for 30 minutes, the pre-emulsified N-hydroxymethyl acrylamide is added to the system within 2.5 hours, and 1% acrylic acid is added at the same time, and the dripping speed is controlled so that it is dripped within 0.5 hours after the addition of N-hydroxymethyl acrylamide. After all the materials are dripped, the temperature is raised to 85°C and kept warm for 1 hour, and then the temperature is reduced to 30-40°C, and the pH is adjusted to 6-7 for discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-bonded cotton adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-bonded cotton adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. In this way, the preparation of high-elastic composite spray-bonded cotton is completed.
[0011] Compared with the prior art, the present invention has the following beneficial effects: The present invention sprays the fiber layer with the prepared core-shell structure spray-bonded cotton adhesive, which can effectively improve the elasticity of the finished spray-bonded cotton. At the same time, during the preparation, the cohesion rate, cross-linking degree, contact angle and elasticity of the adhesive can be guaranteed, and the water absorption rate can also be improved. DETAILED DESCRIPTION
[0012] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0013] The invention relates to a high-elastic composite spray-bonded cotton, comprising a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, ethylene glycol butyl ether, ammonia water, NaHCO 3 、Na 2 CO 3 The mixture comprises, by mass, 30-40 parts of methyl methacrylate, 20-30 parts of n-butyl acrylate, 2-5 parts of styrene, 2-5 parts of N-hydroxymethyl acrylamide, 3-8 parts of acrylic acid, 3-8 parts of disodium alkyl diphenyl ether disulfonate, 1-3 parts of nonylphenol polyoxyethylene ether, 1-3 parts of ammonium persulfate, 0.5-2 parts of ethylene glycol butyl ether, 5-10 parts of aqueous ammonia, 2-5 parts of NaHCO 3 , 0.2-3 parts of Na 2 CO 3 ; N-Hydroxymethyl acrylamide is an industrial product, acrylic acid is analytical grade, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytical grade, ethylene glycol butyl ether is analytical grade, ammonia water is analytical grade, NaHCO3 is analytical grade, Na2CO3 is analytical grade, the fineness in the fiber layer is 6.6-7.7dtex, the length is 51-7mm, the number of crimps is 0.5-0.6 / mm, and the hollowness is 5-10%.
[0014] The mixture includes 30 parts of methyl methacrylate, 20 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 8 parts of acrylic acid, 8 parts of disodium alkyl diphenyl ether disulfonate, 3 parts of nonylphenol polyoxyethylene ether, 3 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 10 parts of ammonia water, 5 parts of NaHCO 3 , 1 part of Na 2 CO 3 .
[0015] The mixture includes 35 parts of methyl methacrylate, 25 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 5 parts of acrylic acid, 5 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 2 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 8 parts of ammonia water, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 .
[0016] The mixture includes 40 parts of methyl methacrylate, 30 parts of n-butyl acrylate, 2 parts of styrene, 2 parts of N-hydroxymethyl acrylamide, 3 parts of acrylic acid, 3 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 1 part of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 9 parts of aqueous ammonia, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 .
[0017] A method for preparing high-elastic composite spray-bonded cotton comprises the following steps: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: Put a thermometer, condenser, stirring paddle and constant pressure dropping funnel into a four-necked flask, then place the four-necked flask in a constant temperature water bath, add emulsifiers such as disodium alkyl diphenyl ether disulfonate and Na 2 CO 3 , styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water, the speed is set to 400r·min -1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , add NaHCO evenly over 15 min. 3 , and keep warm for 20 minutes to complete the seed emulsion, the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer are evenly added to the seed emulsion within 2 hours, and kept warm for 30 minutes, the pre-emulsified N-hydroxymethyl acrylamide is added to the system within 2.5 hours, and 1% acrylic acid is added at the same time, and the dripping speed is controlled so that it is dripped within 0.5 hours after the addition of N-hydroxymethyl acrylamide. After all the materials are dripped, the temperature is raised to 85°C and kept warm for 1 hour, and then the temperature is reduced to 30-40°C, and the pH is adjusted to 6-7 for discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-bonded cotton adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-bonded cotton adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. In this way, the preparation of high-elastic composite spray-bonded cotton is completed. Specific embodiment one: A high-elastic composite spray-bonded cotton comprises a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, ethylene glycol butyl ether, ammonia water, NaHCO 3 、Na 2 CO 3 The mixture includes 30 parts of methyl methacrylate, 20 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 8 parts of acrylic acid, 8 parts of disodium alkyl diphenyl ether disulfonate, 3 parts of nonylphenol polyoxyethylene ether, 3 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 10 parts of ammonia water, 5 parts of NaHCO 3 , 1 part of Na 2 CO 3 ; N-Hydroxymethyl acrylamide is an industrial product, acrylic acid is analytical grade, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytical grade, ethylene glycol butyl ether is analytical grade, ammonia water is analytical grade, NaHCO3 is analytical grade, Na2CO3 is analytical grade, the fineness in the fiber layer is 6.6-7.7dtex, the length is 51-7mm, the number of crimps is 0.5-0.6 / mm, and the hollowness is 5-10%.
[0019] A method for preparing high-elastic composite spray-bonded cotton comprises the following steps: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: Put a thermometer, condenser, stirring paddle and constant pressure dropping funnel into a four-necked flask, then place the four-necked flask in a constant temperature water bath, add emulsifiers such as disodium alkyl diphenyl ether disulfonate and Na 2 CO 3 , styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water, the speed is set to 400r·min-1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , add NaHCO evenly over 15 min. 3 , and keep warm for 20 minutes to complete the seed emulsion, the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer are evenly added to the seed emulsion within 2 hours, and kept warm for 30 minutes, the pre-emulsified N-hydroxymethyl acrylamide is added to the system within 2.5 hours, and 1% acrylic acid is added at the same time, and the dripping speed is controlled so that it is dripped within 0.5 hours after the addition of N-hydroxymethyl acrylamide. After all the materials are dripped, the temperature is raised to 85°C and kept warm for 1 hour, and then the temperature is reduced to 30-40°C, and the pH is adjusted to 6-7 for discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-bonded cotton adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-bonded cotton adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. In this way, the preparation of high-elastic composite spray-bonded cotton is completed. Specific embodiment 2: A high-elastic composite spray-bonded cotton comprises a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, ethylene glycol butyl ether, ammonia water, NaHCO 3 、Na 2 CO 3 The mixture includes 35 parts of methyl methacrylate, 25 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 5 parts of acrylic acid, 5 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 2 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 8 parts of ammonia water, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 ; N-Hydroxymethyl acrylamide is an industrial product, acrylic acid is analytical grade, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytical grade, ethylene glycol butyl ether is analytical grade, ammonia water is analytical grade, NaHCO3 is analytical grade, Na2CO3 is analytical grade, the fineness in the fiber layer is 6.6-7.7dtex, the length is 51-7mm, the number of crimps is 0.5-0.6 / mm, and the hollowness is 5-10%.
[0021] A method for preparing high-elastic composite spray-bonded cotton comprises the following steps: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: Put a thermometer, condenser, stirring paddle and constant pressure dropping funnel into a four-necked flask, then place the four-necked flask in a constant temperature water bath, add emulsifiers such as disodium alkyl diphenyl ether disulfonate and Na 2 CO 3 , styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water, the speed is set to 400r·min -1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , add NaHCO evenly over 15 min. 3 , and keep warm for 20 minutes to complete the seed emulsion, the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer are evenly added to the seed emulsion within 2 hours, and kept warm for 30 minutes, the pre-emulsified N-hydroxymethyl acrylamide is added to the system within 2.5 hours, and 1% acrylic acid is added at the same time, and the dripping speed is controlled so that it is dripped within 0.5 hours after the addition of N-hydroxymethyl acrylamide. After all the materials are dripped, the temperature is raised to 85°C and kept warm for 1 hour, and then the temperature is reduced to 30-40°C, and the pH is adjusted to 6-7 for discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-bonded cotton adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-bonded cotton adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. In this way, the preparation of high-elastic composite spray-bonded cotton is completed. Specific embodiment three: A high-elastic composite spray-bonded cotton comprises a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, nonylphenol polyoxyethylene ether, ammonium persulfate, ethylene glycol butyl ether, ammonia water, NaHCO 3 、Na 2 CO 3The mixture includes 40 parts of methyl methacrylate, 30 parts of n-butyl acrylate, 2 parts of styrene, 2 parts of N-hydroxymethyl acrylamide, 3 parts of acrylic acid, 3 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 1 part of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 9 parts of ammonia water, 5 parts of NaHCO 3 , 2 parts of Na 2 CO 3 ; N-Hydroxymethyl acrylamide is an industrial product, acrylic acid is analytical grade, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytical grade, ethylene glycol butyl ether is analytical grade, ammonia water is analytical grade, NaHCO3 is analytical grade, Na2CO3 is analytical grade, the fineness in the fiber layer is 6.6-7.7dtex, the length is 51-7mm, the number of crimps is 0.5-0.6 / mm, and the hollowness is 5-10%.
[0023] A method for preparing high-elastic composite spray-bonded cotton comprises the following steps: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: Put a thermometer, condenser, stirring paddle and constant pressure dropping funnel into a four-necked flask, then place the four-necked flask in a constant temperature water bath, add emulsifiers such as disodium alkyl diphenyl ether disulfonate and Na 2 CO 3 , styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water, the speed is set to 400r·min -1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , add NaHCO evenly over 15 min 3 , and keep warm for 20 minutes to complete the seed emulsion, the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer are evenly added to the seed emulsion within 2 hours, and kept warm for 30 minutes, the pre-emulsified N-hydroxymethyl acrylamide is added to the system within 2.5 hours, and 1% acrylic acid is added at the same time, and the dripping speed is controlled so that it is dripped within 0.5 hours after the addition of N-hydroxymethyl acrylamide. After all the materials are dripped, the temperature is raised to 85°C and kept warm for 1 hour, and then the temperature is reduced to 30-40°C, and the pH is adjusted to 6-7 for discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-bonded cotton adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-bonded cotton adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. In this way, the preparation of high-elastic composite spray-bonded cotton is completed.
[0024] The performance of the prepared spray-bonded cotton in the present invention is compared with the spray-bonded cotton on the market, wherein the specific embodiments 1 to 3 in the present invention are recorded as embodiments 1-3, and the spray-bonded cotton on the market is recorded as comparative example 1. The following is a comparison table: It can be seen that the spray-bonded cotton prepared by the present invention has good elasticity.
[0025] The present invention sprays the fiber layer with the prepared core-shell structure spray-bonded cotton adhesive, which can effectively improve the elasticity of the finished spray-bonded cotton. At the same time, during the preparation, the cohesion rate, cross-linking degree, contact angle and elasticity of the adhesive can be guaranteed, and the water absorption rate can also be improved.
[0026] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high elastic composite spray-bonded cotton, characterized in that: The invention comprises a fiber layer and a core-shell structure spray-bonded cotton adhesive, wherein the core-shell structure spray-bonded cotton adhesive comprises methyl methacrylate, n-butyl acrylate, styrene, N-hydroxymethyl acrylamide, acrylic acid, disodium alkyl diphenyl ether disulfonate, polyoxyethylene nonylphenol ether, ammonium persulfate, butyl glycol ether, ammonia water, NaHCO3 and Na2CO3, and comprises, by mass, 30-40 parts of methyl methacrylate, 20-30 parts of n-butyl acrylate, 2-5 parts of styrene, 2-5 parts of N-hydroxymethyl acrylamide, 3-8 parts of acrylic acid, 3-8 parts of disodium alkyl diphenyl ether disulfonate, 1-3 parts of polyoxyethylene nonylphenol ether, 1-3 parts of ammonium persulfate, 0.5-2 parts of butyl glycol ether, 5-10 parts of ammonia water, 2-5 parts of NaHCO3 and 0.2-3 parts of Na2CO3.
2. The high elastic composite spray-bonded cotton according to claim 1, characterized in that: The N-hydroxymethyl acrylamide is an industrial product, acrylic acid is analytically pure, disodium alkyl diphenyl ether disulfonate is industrial grade, nonylphenol polyoxyethylene ether is chemically pure, nonylphenol polyoxyethylene ether is chemically pure, ammonium persulfate is analytically pure, ethylene glycol butyl ether is analytically pure, ammonia water is analytically pure, NaHCO3 is analytically pure, and Na2CO3 is analytically pure. The fineness of the fiber layer is 6.6-7.7 dtex, the length is 51-7 mm, the number of crimps is 0.5-0.6 per millimeter, and the hollowness is 5-10%.
3. The high elastic composite spray-bonded cotton according to claim 1, characterized in that: The composition comprises, by mass, 30 parts of methyl methacrylate, 20 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 8 parts of acrylic acid, 8 parts of disodium alkyl diphenyl ether disulfonate, 3 parts of nonylphenol polyoxyethylene ether, 3 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 10 parts of aqueous ammonia, 5 parts of NaHCO3, and 1 part of Na2CO3.
4. The high elastic composite spray-bonded cotton according to claim 1, characterized in that: The composition comprises, by mass, 35 parts of methyl methacrylate, 25 parts of n-butyl acrylate, 5 parts of styrene, 5 parts of N-hydroxymethyl acrylamide, 5 parts of acrylic acid, 5 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 2 parts of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 8 parts of aqueous ammonia, 5 parts of NaHCO3, and 2 parts of Na2CO3.
5. The high elastic composite spray-bonded cotton according to claim 1, characterized in that: The composition comprises, by mass, 40 parts of methyl methacrylate, 30 parts of n-butyl acrylate, 2 parts of styrene, 2 parts of N-hydroxymethyl acrylamide, 3 parts of acrylic acid, 3 parts of disodium alkyl diphenyl ether disulfonate, 1 part of nonylphenol polyoxyethylene ether, 1 part of ammonium persulfate, 2 parts of ethylene glycol butyl ether, 9 parts of aqueous ammonia, 5 parts of NaHCO3, and 2 parts of Na2CO3.
6. A method for preparing a high-elastic composite spray-bonded cotton according to any one of claims 1 to 5, characterized in that: The steps include: S1: Prepare the equipment for preparation: including thermometer, condenser, stirring paddle, four-necked flask with constant pressure dropping funnel, constant temperature water bath, drying oven, spray gun; S2: Preparation of core-shell structure spray-bonded cotton adhesive: A thermometer, a condenser, a stirring paddle and a constant pressure dropping funnel were placed in a four-necked flask, and then the four-necked flask was placed in a constant temperature water bath. Emulsifiers such as disodium alkyl diphenyl ether disulfonate, Na2CO3, styrene, methyl methacrylate, 30 parts of n-butyl acrylate, ethylene glycol butyl ether and ammonia water were added according to the mass fraction at 60°C. The speed was set to 400 r·min -1 , raise the temperature to 80℃ and reduce the speed to 190r·min -1 , evenly drop NaHCO3 within 15 minutes, and keep warm for 20 minutes to complete the seed emulsion, evenly drop the remaining nonylphenol polyoxyethylene ether and ammonium persulfate core layer into the seed emulsion within 2 hours, and keep warm for 30 minutes, add the pre-emulsified N-hydroxymethyl acrylamide into the system within 2.5 hours, and at the same time drop 1% of acrylic acid, control the dropping speed so that it is finished within 0.5 hours after the addition of N-hydroxymethyl acrylamide, after all the materials are added, raise the temperature to 85 ° C and keep warm for 1 hour, then reduce the temperature to 30-40 ° C, adjust the pH to 6-7 and discharge, thereby completing the preparation of the core-shell structure spray-bonded cotton adhesive pair; S3: Spraying treatment of core-shell structure spray-colloid adhesive: Place the fiber layer on a platform, prepare a tabletop, fill the prepared core-shell structure spray-colloid adhesive into the spray gun, adjust the pressure of the spray gun to 0.3-0.5MPa, and spray the fiber layer. After spraying one side of the fiber layer, spray the other side. After the outer wall is completely sprayed, dry it, place it in a drying oven, dry it at 40°C for 10-15 minutes, and then take it out. This completes the preparation of high-elasticity composite spray-bonded cotton.